2014
DOI: 10.1109/tbme.2013.2295381
|View full text |Cite
|
Sign up to set email alerts
|

Movement Stability Analysis of Surface Electromyography-Based Elbow Power Assistance

Abstract: The use of power assistive devices that use surface electromyography (SEMG) signals may be limited by the noisy nature of SEMG signals. The aim of this study was to investigate the variation in human movement stability while the amount of SEMG-based assistive power was changed. A robotic device provided a torque that was proportional to the torque estimated by SEMG for assisting human movements, and 12 volunteers participated in the elbow flexion experiments. The maximum finite-time Lyapunov exponent (MFTLE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 35 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…This may be explained by the fact that the tracking performance of an ankle exoskeleton is not as good as that of a healthy subject, so a subject is able to track a target well when the ankle exoskeleton does not provide assistive torque. In a previous study, Kwon et al ( 2014 ) investigated the variation in human movement stability while varying the assistive torque provided by a robotic device based on the EMG amplitude. They found that movements became unstable because of an increased assistive torque.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the fact that the tracking performance of an ankle exoskeleton is not as good as that of a healthy subject, so a subject is able to track a target well when the ankle exoskeleton does not provide assistive torque. In a previous study, Kwon et al ( 2014 ) investigated the variation in human movement stability while varying the assistive torque provided by a robotic device based on the EMG amplitude. They found that movements became unstable because of an increased assistive torque.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the AACS provides assistive torque through the inner position loop rather than the proportional myoelectric or estimated joint torque. Therefore, compared with conventional EMG control (Song et al, 2013 ; Kwon et al, 2014 ), the PD controller of the AACS can help improve the robustness and stability properties. The AACS can also allow a robot to be controlled in a more natural and human-like way by adjusting the parameters of the inner position loop according to the joint impedance.…”
Section: Discussionmentioning
confidence: 99%